"I don't know what to do. Pray I guess.": Faith and coping with frontotemporal dementia. Issue 3 (3rd July 2018) - Joaquin, Anna Dina L.; Mates, Andrea W.
ABSTRACT: This case study uses participant observation ethnography to provide an in-depth view of what assumptions undergird the religious coping strategies of a caregiver wife whose husband was diagnosed with behavioral variant frontotemporal dementia (bvFTD). Transcripts of interactions and narratives allow for thick descriptions of not just the family's religiousness, but also the caregiver's revealed understanding of her Catholic faith. This understanding not only forms her responses to daily stresses but also to gives hope and meaning to the larger experience of managing her husband's decline. Finally, recommendations are made to clinicians and caregivers.